ANALISIS MEMADU HUKUM ISLAM DAN HUKUM NASIONAL MENGENAI KORUPSI DI INDONESIA - Luluatu Nailul Roja’; Ashif Az Zafi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2020)
Corruption is a criminal act of implementing the state. This crime has been carried out systematically, structurally, and massively. The effect is not only making the country's finances worse, but also risking the financial aspects, natural resources, and dignity of the next generation. Fuqaha has had dialogues about corruption, conflicts within and above which are different. This article discusses the challenges of discourse, negation and punishment of corruption in Indonesia. Based on in-depth research, Fuqaha expressed the construction of Studio Sariqah, Ghulul, Risywah, Ghasab, etc., substantially, has links to security investigations in Indonesia. That is why the dedication of fiqh in the eradication of corruption in Indonesia becomes evident, related to the concept, sanctions, and eradication of corruption and its consequences in Indonesia. Keywords: corruption, KPK, sariqah, ghulul, Ta'zir.